Iran Nuclear Armed: Implication for Regional Nuclear Proliferation - etinagbedia, Goodluck (International Journal of Public Administration Studies, 2024)
This study looks into how Iran's nuclear weapons might affect the spread of nuclear weapons in the Middle East region. The international discourse surrounding Middle East issues has intensified, resulting in a closer connection between the security systems of the region and the global arena. For security and stability to exist in the Middle East, non-proliferation of nuclear weapons and disarmament are essential. If more breakouts are to be avoided, addressing them must be done immediately. This needs to be completed thoroughly and without bias or preference. The historical research design was used in this investigation. Among other things, the study found that the Islamic Republic finds nuclear weapons appealing due to two main factors: deterrence and regional hegemony. Iranian efforts to develop nuclear weapons capabilities have been prompted by the current imbalance of power distribution in the Middle East, the study concludes. It suggests, among other things, that Iran-US relations should be given top priority and that, should they continue to be adversaries, little progress will likely be made in improving bilateral ties in the Persian Gulf and the Middle East. This is the most efficient method of ensuring the security as well as survival of the regime and state. When it comes to backing initiatives meant to bring peace and stability back to the Middle East, including potential regional security frameworks, the UN ought to be more proactive and assertive.